2014
DOI: 10.1038/jcbfm.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cerebral Blood Flow Acquired by Simultaneous [15O]Water Positron Emission Tomography and Arterial Spin Labeling Magnetic Resonance Imaging

Abstract: Until recently, no direct comparison between [15O]water positron emission tomography (PET) and arterial spin labeling (ASL) for measuring cerebral blood flow (CBF) was possible. With the introduction of integrated, hybrid magnetic resonance (MR)-PET scanners, such a comparison becomes feasible. This study presents results of CBF measurements recorded simultaneously with [15O]water and ASL. A 3T MR-BrainPET scanner was used for the simultaneous acquisition of pseudo-continuous ASL (pCASL) magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
138
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 38 publications
11
138
5
3
Order By: Relevance
“…Other studies have found moderate to good correlations (r ϭ 0.4 -0.8) between pseudocontinuous ASL and PET imaging for pCBF measurements. 4,27,28 On the contrary, Henriksen et al 29 showed a large underestimation of ASLbased pCBF (75%) compared with the estimation by PCMRI and no correlation between the 2 methods. One explanation for this result might be that they used a model-free pulsed-ASL method.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have found moderate to good correlations (r ϭ 0.4 -0.8) between pseudocontinuous ASL and PET imaging for pCBF measurements. 4,27,28 On the contrary, Henriksen et al 29 showed a large underestimation of ASLbased pCBF (75%) compared with the estimation by PCMRI and no correlation between the 2 methods. One explanation for this result might be that they used a model-free pulsed-ASL method.…”
Section: Discussionmentioning
confidence: 95%
“…[37][38][39] Such reference image acquisition can and will be included in future studies. Since the average gray matter perfusion is approximately 70 ml/100g/min for normal healthy young volunteers, 40 the absolute perfusion signal fluctuations can be estimated from this population average and the reported signal fluctuation percentage in this paper. An additional benefit of ASL for study of resting state networks is the reduction of non-neural noise sources observed with BOLD.…”
Section: Discussionmentioning
confidence: 99%
“…53 Also, in neuropsychiatric diseases such as Alzheimer disease, ASL and FDG-PET have been shown to detect similar, but not identical, perfusion/metabolism abnormalities, 50,51 suggesting complementary and nonredundant information provided by both imaging modalities. Modality-dependent characteristics, however, cannot fully account for our finding of lower rCBF in the subgenual part of the ACC.…”
Section: Discussionmentioning
confidence: 99%